STUDENTS’ PERCEPTION TOWARD ENGLISH TEACHERS’ QUESTIONING IN CLASSROOM INTERACTION - Rezky Uspayanti (JLE: Journal of Literate of English Education Study Program, 2020)
This research focused on English teachers’ questioning and students’ perception toward teachers’questioning in classroom interaction. The qualitative method was used in this research thatemphasized on discourse analysis. Two English teachers and twenty students in Senior High School 1Pinrang were the samples that were taken through purposive sampling technique. There were threesteps in collecting data such as video recording, observation checklist and interview. In process ofcollecting data, there were some steps namely observing the teaching and learning process tofind out the questioning strategies used by English teachers, recording the data by usingaudio and video recording, filling the observation checklist while recording. Thus, theinterview was done to find out the students’ perception toward the teachers’ questioning. Asthe result, there were three types of questioning that were used by the English teachers in classroominteraction namely procedural, convergent and divergent question. Furthermore, twenty students whowere the sample in this research gave positive perception toward the English teachers’ questioningsthat teachers’ questionings were the way to motivate in learning process, improve the interaction andthe English ability especially in vocabulary.